Poster 268: Allogeneic, Off The Shelf, Bone Marrow derived, Pooled, Mesenchymal Stromal Cells – A Potential Break through Therapy for Grade II & III Osteoarthritis Knee Management. Issue 7 (30th July 2022) - Maheswari, Sunil; Cherian, Joe; Goni, Vijay; Sharma, Arun; Tripathy, Sujith; Talari, Keerthi; Pandey, Vivek; Sancheti, Parag; Singh, Saurabh; Bandyopadhyay, Syamasis; Shetty, Naresh; Kamath, Surendra; et al.
Objectives: Osteoarthritis (OA) is the most prevalent joint disease and a common cause of joint pain, functional loss, and disability. We had conducted a randomized, double blind, multi-centric, Phase 3 study (Registered prospectively in Clinical Trial Registry of India: CTRI/2018/09/015785. Study has been approved by Drug Controller General - India) to assess the efficacy and safety of intra-articular administration of stempeucel® (Allogeneic, Bone Marrow derived, Pooled, Mesenchymal Stromal Cells) in Patients with Grade II and III Osteoarthritis of Knee. Methods: 146 patients of primary osteoarthritis having Grade II & III OA based on Kellgren and Lawrence radiographic criteria were randomized to stem cell and placebo group in a ratio of 1:1. Patients having subchondral sclerosis (by X ray), complete tear of ACL / PCL, grade 3 meniscal tears and exclusive patellofemoral arthritis (by MRI) were excluded from the study. 73 patients each received either a single intra-articular injection of stempeucel ® (25 million cells) followed by 20mg hyaluronan or Placebo (saline) followed by 20mg hyaluronan under ultrasound guidance. These patients were followed up for 12 months with 7 visits. The primary end point was evaluation at one year follow up of WOMAC Composite Index score (score range 0 – 2400) as compared to the placebo arm. Secondary end points were – WOMAC sub-scores (pain [0-500], stiffness [0-200] & physical function [0-1700]), VAS [0-100] & MRI assessment (by 3T imaging) of the articular cartilage (T2 mapping [assessment of hydration & cartilage quality], volume [measured using dicom reader and calculated at midportion of medial and lateral tibiofemoral compartment] & thickness [measured at mid points of 20 predetermined sub-regions of two compartments]). Radiological evaluation was done by an Independent, blinded radiologist. Results: The mean weight and BMI of patients in stempeucel® and placebo arms were 67.1 kg & 26.5 and 65.4 kg and 26.2 respectively. Majority of patients in the study were females (Female vs Male: 64.4% vs. 35.6% for stempeucel® arm, 69.9% vs. 30.1% for placebo arm). Total 74 and 72 patients accounted from Grade II and Grade III OA respectively. 65 patients from stempeucel® and 68 patients from placebo arm completed 12 month follow up period. WOMAC composite index, the primary end point of the study, showed significant improvements in cell arm as compared to placebo at month 6 (mean difference: -349.91; 95% CI [-493.00, -206.81], P<0.0001; percentage change: -35%) and month 12 (mean difference: -632.74; 95% CI [-791.57 - -473.91], P<0.0001; percentage change: -44.3%) (Table 1, Figures 1 & 2). Additionally stempeucel® significantly improved WOMAC pain, stiffness, physical function and VAS scores at 6 and 12 months (P<0.0001 for all parameters) in stempeucel® arm as compared to placebo arm. Further Mixed Model Repeated Measures analysis was done and it was seen that the reduction in WOMAC total score in stempeucel® group was statistically significant when compared to placebo but MRI grade (Grade II or III) has no impact on the overall treatment effect (P=0.9658).T2 mapping shows that there is no worsening of the deep cartilage in the medial femoral tibial compartment of the knee in stempeucel® arm at month 12 follow up (change from baseline -0.6 ms, mean value 36.1 ms, P= 0.6188) within the group whereas in placebo arm there is significant and gradual worsening of the cartilage seen within the group at month 12 (change from baseline: 10.8 ms, mean value 47ms, P<0.0001) (Figure 3). Cartilage volume analyzed by Generalized Estimating Equations (GEE) method shows there is increase in average cartilage total volume of 34.07 units (95% CI [-63.08, 131.22], P= 0.492) in stempeucel® arm as compared to placebo arm irrespective of time. No change in cartilage thickness (P=0.5776 at month 12) and morphological score (P=0.7115 at month 12) were seen. CTX – II (measure of C-terminal crosslinked telopeptide type II collagen secreted into urine and indicative of disease progression) showed decrease in levels (-7.79 pg/ml, 95% CI [-96.18, 80.60], P=0.863) in stempeucel® arm irrespective of time when analyzed using GEE method. Anti – inflammatory marker IL-10 in serum was measured and within the group, its levels in placebo group decreased by -0.228 pg/ml at month 12 (p=0.0156) whereas in the stempeucel® group it increased by 0.051 pg/ml (p=0.0625). The reduction in intake of analgesic were monitored and it was found that there is no significant difference in intake or reduction of analgesics in both the groups (11 patients from stempeucel ® and 9 patients from placebo group had reduction in intake of analgesics). There was 49 AEs in 24 patients in the stempeucel® group and 33 AEs in 20 patients in the placebo group. 5 AEs (4 & 1 in stempeucel® & placebo arm respectively) were possibly / probably related to the study drug and were – injection site swelling and pain. These improved within one week of symptomatic therapy. No significant differences were found in other safety parameters like vital signs, ECG, physical examination and laboratory parameters. Conclusions: Allogeneic, pooled BM-MSCs (stempeucel®) has proven to be safe and effective for treatment of Grade II and Grade III Osteoarthritis of knee. The intervention is simple, easy to administer, does not require surgery, provides sustained relief of pain, stiffness, improves physical function, prevents worsening of cartilage quality and improves cartilage volume for at least 12 months follow up.